Povezave med razjedo zaradi pritiska in ohranjanjem integritete kože pacienta v intenzivni zdravstveni obravnavi - Emeđi, Dragica (Obzornik zdravstvene nege, 2015)
Introduction: The research aims to demonstrate the multidimensional needs and potential high-risk factors for developing pressure ulcer in adult patients in the intensive care. Methods: The analysis and synthesis of the evidence review from the EMERALD, CINAHL, PubMed, and ProQuest database were employed in the research. The search terms used were: "quality of care", "pressure ulcer", "prevention and treatment of pressure ulcers", "skin integrity critical care patients". The filtering search criteria were: the period from 2010 to 2013, full-text articles and articles in English. 280 search results met the initial criteria; 40 of those were reviewed and presented in accordance with the Cochrane Database of Systematic Reviews. The evidence quality was assessed according to the hierarchy of the research evidence. Results: 191 codes were identified and grouped into 11 content categories: intensive care setting - characteristics of some pressure ulcer development risk factors, duration of stay in the unit, vasoactive agents, gender, age, administrative diagnostic category, bed, mattress, Waterlow scale, pressure ulcer and the importance of stage I pressure ulcer. Discussion and conclusion: The research demonstrates the importance of introducing proactive measures to maintain the integrity of the skin of the patient. It focuses on the theoretical aspect of the tissue vitality and the promotion of the quality care. Further researches are needed for a deeper insight into the numerous other risks and efficient skin vitality programs.
Keywords: environment factors; importance; kakovost; kazalniki; kožna integriteta; meaning; okoljski dejavniki; pomen; pressure ulcer; quality indicators; quality of health care; razjeda zaradi pritiska; skin integrity; zdravstvene oskrba